The Effect of Compensation and Motivation on Employee Performance CV. Giri Jaya Perkasa - Samodro, Reno Bagus; Kustini, Kustini (Universitas Pamulang, 2022)
This study aims to determine (1) the effect of compensation on employee performance, (2) the effect of motivation on employee performance at CV Giri Jasa Perkasa. The population in this study were all employees at CV Giri Jasa Perkasa, totaling 50 people in the operational section. The sampling technique used is a saturated sample by taking the entire population without having to draw a research sample so that a sample of 50 employees is obtained. The type of data used in the form of a questionnaire as a data collection method which is processed by the Partial Least Square (PLS) analysis method. Based on the results of this study, it shows that (1) compensation has a significant effect on employee performance, (2) motivation has a significant effect on employee performance at CV Giri Jasa Perkasa.